2014
DOI: 10.1080/17583004.2015.1020011
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for radical emissions reduction through behavior and lifestyle change

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Versions of published Taylor & Francis and Routledge Open articles and Taylor & Francis and Routledge Open Select articles posted to institutional or subject repositories or any other third-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 123 publications
3
71
0
1
Order By: Relevance
“…Such transformations, however, have to be rooted in changes towards low(er)-carbon individual lifestyles. Research on conventional behavior change strategies, such as information and communication campaigns, social marketing or nudging show positive effects, however only to a limited extent [10]. Moreover, it has been found that individual carbon footprint levels, particularly in the domain of housing and transportation, only marginally relate to pro-environmental motivations, whereas individuals' income levels have a much stronger predictive power (e.g., [5,11]).…”
Section: Introductionmentioning
confidence: 99%
“…Such transformations, however, have to be rooted in changes towards low(er)-carbon individual lifestyles. Research on conventional behavior change strategies, such as information and communication campaigns, social marketing or nudging show positive effects, however only to a limited extent [10]. Moreover, it has been found that individual carbon footprint levels, particularly in the domain of housing and transportation, only marginally relate to pro-environmental motivations, whereas individuals' income levels have a much stronger predictive power (e.g., [5,11]).…”
Section: Introductionmentioning
confidence: 99%
“…But in the fields such as being close to the nature and looking after plants, neighborhood residents spontaneously perform low-carbon related behaviors. (2) e results in this paper revealed people's level of participation in low-carbon behaviors at the neighborhood scale, while many previous literatures emphasized on the impact of individual low-carbon behavior change [12,18,50]. It was discovered that most respondents cared about the low-carbon impact on their daily lives and concentrated their participation in low-carbon behaviors from traditional products such as disposable chopsticks, toiletries, and plastic bags, though some expressed their difficulties to do so in their daily lives.…”
Section: Discussion and Suggestionsmentioning
confidence: 59%
“…To meet these targets the UK faces 'an urgent need for completely new energy policy across a range of areas' (UK Committee on Climate Change, 2016). It is thought by many that a reliance upon individual-level voluntary behavioural responses by the wider public can only make a limited contribution to meeting those targets (Capstick et al 2014;Shove, 2010;Capstick et al 2015;Chamberlin et al 2015). At the same time there has, to date, been political reluctance in the UK to introduce more radical top-down policies to structure emissions reduction, such as carbon taxation or personal carbon trading (Chamberlin et al 2015;Lorenzoni et al 2008).…”
Section: Introductionmentioning
confidence: 99%